2021
DOI: 10.3389/fpsyg.2021.696552
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Online Identity Reconstruction

Abstract: The tremendous development of the Internet enables people to present themselves freely. Some people may reconstruct their identity on the Internet to build an online identity that is partly or even completely different from their real identity in the offline world. Given that research on online identity reconstruction is fragmented, it is important to evaluate the current state of the literature. In this paper, a review of literature related to online identity reconstruction was conducted. This study summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 68 publications
1
4
0
2
Order By: Relevance
“…In our sample data, this type of person would be classified as provaccine instead of antivaccine in the HPS but would also contribute to the negative perceptions found on Twitter. These findings also align with prior research that suggested an individual's web-based persona may differ from their offline identity [32][33][34]. This offline identity is often limited by physical, emotional, and financial circumstances that may be beyond an individual's control [33,[35][36][37].…”
Section: Study Findings In Contextsupporting
confidence: 86%
See 1 more Smart Citation
“…In our sample data, this type of person would be classified as provaccine instead of antivaccine in the HPS but would also contribute to the negative perceptions found on Twitter. These findings also align with prior research that suggested an individual's web-based persona may differ from their offline identity [32][33][34]. This offline identity is often limited by physical, emotional, and financial circumstances that may be beyond an individual's control [33,[35][36][37].…”
Section: Study Findings In Contextsupporting
confidence: 86%
“…This offline identity is often limited by physical, emotional, and financial circumstances that may be beyond an individual's control [33,[35][36][37]. However, individuals have complete control over the identity they choose to present on the web [32][33][34]. The inverse relationship between the vaccine-hesitant measure in the HPS and percentage of tweets expressing a negative sentiment may have also been due to the use of sarcasm in tweets, where the text itself contradicts what is actually meant by the user [38].…”
Section: Study Findings In Contextmentioning
confidence: 99%
“…Nepaisant mokslinių darbų gausos tapatybės (Bell, 1999;Bauman, 2001;Donskis, 2006;Rapolienė, 2008;Repšienė, 2018;Huang, Kumar & Hu, 2021) ir tatuiruočių (Buss & Hodges, 2017;Demello, 2017;Dedoe, 2021;Rees, 2021;Ojeda et al, 2022) temomis, pasigendama tarpdisciplininio požiūrio į tapatybės tyrinėjimą, sujungiančio abi patirties formas, kurios formuoja asmens tapatumą -tiesioginės juslinės ir skaitmeninės patirties, kartu atkreipiant dėmesį į šiuolaikinius sociokultūrinius kontekstus. Todėl svarbu nagrinėti tapatybę, neatskiriant jos formų viena nuo kitos (pavyzdžiui, suvokiant virtualią tapatybę ne kaip atskirą tapatumą) ir žvelgiant į ją iš tarpdisciplininės perspektyvos.…”
Section: įVadasunclassified
“…There are main topics that tend to show the identity of a teenager in social interactions in cyberspace, one of which is identity. Issues that arise from the main topics in the sub-theme of identity are insults, personality, puberty, and achievement (Huang et al, 2021).…”
Section: Identity Subthemementioning
confidence: 99%